Issues and challenges in offering muḍārabah and mushārakah products in Islamic finance - Asmadi Mohamed Naim,; Mahyuddin Abu Bakar,; Muḥammad Nasri Md. Hussein,; Mohamad Noor Habibi Long, (Penerbit Universiti Kebangsaan Malaysia, 2016)
The study aims to explore the views of scholars, bankers and entrepreneurs in promoting muḍārabah and mushārakah based contracts and to analyse their views to strengthening those practises. The study utilized qualitative research approach which consists of document analysis, interviews and observations in few phases. The study found few industrial concerns such as the needs on checks and balances in muḍārabah and mushārakah to avoid failure; the lacking of some good qualities and hence certain conditions must be imposed on entrepreneurs if they want to conduct business based on mushārakah or muḍārabah contracts. In addition, although all respondents agreed that the ḍamān concept is actually contrary to the concept of muḍārabah (muqtaḍā al-ʿaqd), they still stress the need for a mechanism to make entrepreneurs serious in conducting the business. However, the disappointing conclusion derived from the interviews is that the industry is quite reluctant to enhance their participation in muḍārabah- and mushārakah-based products.